Evaluation of Lignocellulosic Substrates on Productivity of Pearl Oyster Mushroom (Pleurotus ostreatus) - , Monalisa Sahu; , Niranjan Chinara; , Saudamini Swain; , Anita Priyadarshini; , Pravasini Behera; , Bibhuti Bhusan Sahoo (Archives of Current Research International, 2025)
Among the oyster mushrooms, Pearl oyster mushroom (Pleurotus ostreatus) is one of the important edible mushrooms cultivated in India. It can be grown on different lignocellulosic substrates. However, its productivity depends upon the nature and the composition of the substrates. Therefore, locally available ten different agri-wastes such as maize stalk, sugarcane bagasse, rice husk, saw dust, banana pseudo stem, groundnut haulm, paper, finger millet stalk, sesame stalk and paddy straw were collected and evaluated for their ability to produce mushroom. The trial was conducted in Centre of Tropical Mushroom Research and Training (CTMRT), OUAT, Bhubaneswar. The substrates were analysed for carbon, nitrogen, cellulose, lignin percent before mushroom production. The data on days to spawn run, pin head initiation, first harvest, biological efficiency (%), average number of fruit bodies per bag, yield (g / bag) along with morphometrics were recorded and analysed with Randomised Block Design using MS-Excel. Highest production of 1366.67 g mushroom per 2kg dry substrate with an average of 246.40 numbers of mushrooms was realised from banana pseudo stem followed by paddy straw (1246.67 g, 240.27 numbers of mushrooms). Minimum time taken, 32.60 days for mushroom production observed in case of finger millet stalk followed by sugarcane bagasse (32.67 days). From the experiment, it was also observed that a range of 40 to 60 C:N ratio and higher cellulose and lignin ratio of the substrates favoured maximum productivity of oyster mushroom.